Fatty acid methyl esters synthesis from non-edible vegetable oils using supercritical methanol and methyl tert-butyl ether. (15th April 2017) - Lamba, Neha; Modak, Jayant M.; Madras, Giridhar
Graphical abstract: Highlights: FAMEs were synthesized from non-edible oils using supercritical MeOH and MTBE. Effect of time, temperature, pressure and molar ratio on conversions was studied. Rate constants of reaction with methanol and MTBE differ by an order of magnitude. Non-catalytic supercritical reactions are one order faster than acid catalyzed synthesis. Abstract: Fatty acid methyl esters (FAMEs) are useful as biodiesel and have environmental benefits compared to conventional diesel. In this study, these esters were synthesized non-catalytically from non-edible vegetable oils: neem oil and mahua oil with two different methylating agents: methanol and methyl tert -butyl ether (MTBE). The effects of temperature, pressure, time and molar ratio on the conversion of triglycerides were studied. The temperature was varied in the range of 523–723 K with molar ratios upto 50:1 and a reaction time of upto 150 min. Conversion of neem and mahua oil to FAMEs with supercritical methanol was found to be 83% in 15 min and 99% in 10 min, respectively at 698 K. Further, a conversion of 46% of mahua oil and 59% of neem oil was obtained in 15 min at 723 K using supercritical MTBE. The rate constants evaluated using pseudo first order reaction kinetics were in the range of 4.7 × 10 −6 to 1.0 × 10 −3 s −1 for the investigated range of temperatures. The activation energies obtained were in the range of 62–113 kJ/mol for the reaction systems investigated. The supercritical synthesis was found to be superior to the catalytic synthesis of the corresponding FAMEs.